Health Education (HE) Effectiveness Towards Knowledge and Behavior of the Treatment of Kanguru Method (PMK) in Public Women in Perinatology Room Luwuk Hospital, Banggai District, Central Sulawesi Province - Lisna Bte Baharuddin; Candra Wahyuni (Journal for Quality in Public Health, 2020)
Background: Up to now, the number of preterm births in Indonesia has reached 10-15% of total births each year. The results of a preliminary study conducted by researchers on November 11-16 2019 in the Perinatology Room at Luwuk Regional Hospital, Banggai District, Central Sulawesi Province, with interviews with 10 infant mothers, it was found that 5 babies said they did not know about treatment using the kangaroo method. The statement of one baby mother said that the mother's knowledge was still low about FMD because the kangaroo method was still considered by the mothers. The research objective was to determine the effectiveness of Health Education (HE) on knowledge about Kangaroo (PMK) treatment of postpartum mothers in the perinatology room of Luwuk Regional Hospital, Banggai Regency, Central Sulawesi Province. Methods: This study used a one group pre-test-post-test design. The number of samples is 35 respondents. Sampling using Accidental Sampling technique. Statistical test using Paired Samples T-Test. The results showed that the pre-test score of knowledge obtained an average of 45.57 and the post-test score of knowledge obtained an average of 74.43. Meanwhile, the pre-test behavior score obtained an average of 43.10 and the post-test behavior score obtained an average of 67.62. The results of the Paired Samples T-Test for knowledge showed a significance value of 0.000 <0.05 and behavior known a significance value of 0.000 <0.05. Conclusion: that there is an average difference between the Pre Test and Post Test values, which means that Health Education (HE) can be said to be effective in increasing knowledge and behavior about Kangaroo Method Care (PMK) for postpartum mothers in the Perinatology Room of Luwuk Regional Hospital, Banggai Regency, Central Sulawesi Province .